Pelatihan Dasar Pengelolaan Keuangan Ibu Rumah Tangga Kelurahan Pematang Gubenur Bengkulu - Isma Coryanata; Indah Oktari Wijayanti; Madani Hatta; Abdullah Abdullah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Household financial management is an important aspect of daily life that is often overlooked or does not receive serious attention. This is even though it plays a major role in determining the economic well-being of the family. Given the complexity of household life involving various needs and expenses, effective financial management is essential to achieving long-term goals and improving the quality of family life. Good management can help overcome various economic challenges and prepare families for unexpected financial conditions.